Effects of vibration therapy with routine physical therapy on pain, balance, and functional disability in diabetic neuropathy patients: a randomised controlled trial - Sajawal Bashir; Jamil, Ayesha; Ali, Sarwat (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the impact of integrating vibration therapy with standard physical therapy on pain levels, balance, functional impairment, and overall patient satisfaction among individuals with diabetic neuropathy. Method: The single-blind, randomised controlled trial was conducted from September 2022 to February 2023 at the Physiotherapy Department of Omar Hospital, Lahore, Pakistan, and comprised patients of either gender aged 40-75 years having diabetic peripheral neuropathy. The participants were randomised using computer-generated numbers into group A receiving routine physical therapy only, and group B receiving vibration therapy with routine physical therapy. Each intervention lasted 12 30-minute sessions over 2 weeks. Assessment was done at baseline, and at end of 1st and 2nd week for pain, balance, functional disability and satisfaction level using standard tools. Data was analysed using SPSS 21. Results: Of the 72 patients with mean age 59.2±9.47 years and mean duration of diabetes 14.23±6.4 years, 40(56%) were males and 32(44%) were females. Each group had 36(50%) subjects. At the baseline, there were no significant differences between the groups (p>0.05). Intergroup comparison for pain, functional disability were significantly better in group A compared to group B (p<0.05), but balance and patient satisfaction were not significantly different post-intervention (p>0.05). Intragroup improvements post-intervention were significantly better compared to baseline values (p<0.05). Conclusion: Vibration therapy was found to be better than routine physical therapy in terms of addressing pain and functional disability. RCT registration: The study was registered at ClinicalTrials.gov (Trial #: NCT05580705 Date of Approval: October 14, 2022). Link: https://clinicaltrials.gov/study/NCT05580705.